2021
DOI: 10.1186/s12955-021-01773-1
|View full text |Cite
|
Sign up to set email alerts
|

The client satisfaction with device: a Rasch validation of the Arabic version in patients with upper and lower limb amputation

Abstract: Background The Client Satisfaction with Devices (CSD) module of the Orthotics and Prosthetics Users’ Survey is an extensively used questionnaire that measures patients’ satisfaction with orthosis and prosthesis. However, the validated version for Arabic speakers (CSD-Ar) is only applicable for orthosis users. Objectives The aim of this study was to evaluate the psychometric proprieties of the CSD-Ar for prosthetics users. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 25 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…The remaining studies [5,14,17,18,21,22] included eight of the 11 original items (the first seven items and item #nine, i.e. ‘Pain free to wear’), in agreement with Jarl et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining studies [5,14,17,18,21,22] included eight of the 11 original items (the first seven items and item #nine, i.e. ‘Pain free to wear’), in agreement with Jarl et al .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in 2019 and 2021, three articles used the eight-item CSD: two Rasch studies validated the cross-culturally translated and adapted version in the Slovene language, and the Arabic version on prosthesis users [5,22], whereas a Canadian study used the CSD American English version as a reference for validating another satisfaction score (the Orthosis Comfort Score) [21].…”
Section: Discussionmentioning
confidence: 99%
“…17 The CSD-Ar consists of 8 items addressing fitting, weight, comfort, donning, appearance, durability, skin abrasion and irritation, and pain. 17 Respondents have rated the CSD-Ar items on a 4-point Likert scale between 1 (strongly agree) and 4 (strongly disagree). Thus, higher CSD-Ar scores indicate less satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional study was designed. The CSD-Ar was used for this purpose, 17 which was validated by Bakhsh et al 17 They concluded the confidence of using CSD-Ar to assess the satisfaction of the prosthetic users. 17 The CSD-Ar consists of 8 items addressing fitting, weight, comfort, donning, appearance, durability, skin abrasion and irritation, and pain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation